Relasi Kuasa Keagamaan sebagai Strategi Pemenangan Pasangan Bobby-Aulia Pilkada Kota Medan - Junaidi, Junaidi; Fuhaidah, Ulya (FIKRAH, 2022)
This paper presents about the religious politics carried out by the Bobby-Aulia couple in winning the Medan City Election. Data was collected by interviewing the informants consisting of the Bobby-Aulia pair's success/winning team. From the interviews conducted, it was found that the political religious communication strategy carried out by the Bobby-Aulia couple in winning the Pilkada was by building and strengthening power relations in religious organizations by packaging political messages promising not to be nepotism in the election of officials, and to collaborate between religious communities and make a plural society as a force in the development of the city of Medan. Using campaign jargon with religious language, namely 'Medan Berkah' to show emotional closeness to Islamic groups as the majority voters. In addition, political communication through the pulpit of da'wah by consolidating the clerics who are indirectly involved in the winning machine.